2016
DOI: 10.1111/raq.12151
|View full text |Cite
|
Sign up to set email alerts
|

Perceived versus real toxicological safety of pangasius catfish: a review modifying market perspectives

Abstract: Mass media reports suggest that pangasius (Pangasianodon hypophthalmus) is ‘full of poison’ because it is able to survive in the ‘heavily polluted Mekong River’ and contains pesticides and veterinary treatment chemicals. However, most of these claims are not substantiated with scientific evidence. To assess the safety of pangasius consumption, a full toxicological risk assessment was performed. The results obtained were compared to toxicity claims made in a selection of media reports. Information on contaminan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 33 publications
0
10
0
Order By: Relevance
“…In reality, cause and effect are probably of different origin, as Swiss products simply do not need an ecolabel for market access. In contrast to the mentioned pangasius, which suffers under a bad reputation mostly due to false claims (Murk et al 2018), Swiss sh are appreciated regardless of their sustainability performance.…”
Section: Discussionmentioning
confidence: 97%
“…In reality, cause and effect are probably of different origin, as Swiss products simply do not need an ecolabel for market access. In contrast to the mentioned pangasius, which suffers under a bad reputation mostly due to false claims (Murk et al 2018), Swiss sh are appreciated regardless of their sustainability performance.…”
Section: Discussionmentioning
confidence: 97%
“…A more concerning disease issue associated with P. hypophthalmus is that many of these diseases and parasitic infections are There have been recent reports of elevated mercury levels in native P. hypophthalmus populations and in imported fish for consumption, which could make aquaculture of this species in Turkey preferable (Ferrantelli et al, 2012;Rodríguez et al, 2018). That said, a recent, full toxicological risk assessment concluded that consumption of P. hypophthalmus available on the European market does not pose any concern for the health of the consumer (Murk, Rietjens, & Bush, 2018). Recent economic evaluations have suggested that importation of P. hypophthalmus as fillets to Turkey is more profitable than rearing the species (E. Ercan, pers.…”
Section: Discussionmentioning
confidence: 99%
“…For example rice-fish culture, where both are produced in the same system at the same time, and for which chemical control of rice pests is required is a good example of this. An important issue ignored by many media polemics is the assessment of comparative risk (Murk et al, 2016). Many studies have indicated that the relative risk from infectious agents, or chemical contamination is many times higher in wild unmanaged stocks than farmed seafood in Asia and this is borne out through the regular monitoring (RASFF) by the EU on imported seafood .…”
Section: Public Health Issuesmentioning
confidence: 99%